Drinking water preference among students in UiTM Perlis using fuzzy AHP / Syahirah Ali Munawar - Ali Munawar, Syahirah (2021)
Many customers around the world, particularly Malaysians, have turned to bottled water as their primary source of potable water. This research was performed to determine the best and most preferred brands of mineral bottled water available in UiTM Arau, Perlis in terms of its advantages and everyday mineral content. The decision-making method used by multi-criteria is the FAHP method as an approach to problem of selection bottled with mineral water. In this paper the mineral water brands bottled namely "Spritzer," "Bleu" and "Ice Mountain" are analyzed and presented as sold in UiTM Perlis. The criterion given is price, availability, taste, water source and packaging. Comparison is made between these three brands in order to decide which of these brands is more favourable and desirable among UiTM Perlis students based on the weight of alternatives regarding the criteria. The result displays that Spritzer has the greatest total score with a weight of 0.439. The analysis shows that the "Spritzer" brand is better compared to the other two daily life consumption brands, which weight is 0.439 with five criteria. Bleu, however, offers the better weighty flavour, 0.386 of those two brands of mineral water bottles. This study will benefit marketers and consumers by helping them make educated decisions on choosing the most appropriate mineral water bottled for consumption in keeping with their health concerns in these times.